Content Management Strategy of Instagram Social Media Koneksi Studio in Attracting Consumer Interest in 2024 - Rais, Hafid Zuldin; Aly Aulia; Dhimas Aryo Vipha Ananda (Jogjakarta Communication Conference (JCC), 2025)
Social media has become an important marketing tool for businesses to attract consumers. Instagram, as one of the popular visual platforms, has become an effective marketing tool for the photography industry, including Koneksi Studio. This research aims to analyse the Instagram social media management strategy applied by Koneksi Studio in attracting consumers in 2024. The theory used is The Circular Model of SOME by Regina Luttrell in her book social media How to Engage, Share, and Connect. This research method is descriptive with a qualitative approach. The data collection technique is an interview with the manager of Koneksi Studio and the social media specialist of Koneksi Studio. This research uses source triangulation for data validity techniques. From the results of the study, it is known that content management on Instagram social media, the share aspect starts with understanding the purpose of using social media for studio connections. The optimise aspect, namely by making a schedule of posting hours and utilising the features available on Instagram. The management aspect is done by managing and evaluating Instagram content regularly. In the engagement aspect, namely establishing good relationships with online communities such as involving influencers, and also communicating with followers via Direct Message to get instagram exposure for the content produced.